Une typologie des processus de concertation lors de l’élaboration des cartes d’aléas littoraux - Céline Perherin (Éditions en environnement VertigO, 2017)
The development of primary coastal risks prevention plans, identified after Xynthia storm in 2010, highlighted debates, often conflicting, between State and territorial authorities about hazard maps. Not only a state of knowledge, developed in a specific way in order to take risks into account in spatial planning, hazard mapping integrates dialogue process, managed by State services. The analysis of these dialogues process during coastal hazards mapping provides an opportunity to purpose a typology. This typology is based on a questionnaire survey of State services and the implementation of two analysis methods, a qualitative comparative analysis and a multiple correspondence analysis. It is mostly characterised by the level of technical debate between stakeholders during mapping and the type of involved stakeholders. The conflict level, linked to the climate of confidence between stakeholders, also characterises these dialogue process. The stakeholders’ adherence to the natural risks prevention general principles, technically translated in hazard mapping, also indirectly influences the debate.